Effect of Grape Seed Extract Powder on Shelf Life of Superchilled Chicken Sausage - Dhagare, L. G.; Rathod, K. S.; Badhe, S.R.; Patil., P. S. (Journal of Meat Science, 2022)
The shelf life of chicken sausage was assessed by incorporating 0.25% grape seed extract powder (GSEP) under superchilling storage and compared with chicken sausages incorporated with BHT and Control (without any antioxidant). The moisture, pH, peroxide value in GSEP treated samples increased significantly (P
Keywords: Grape seed extract powder; Synthetic antioxidants; Superchilling; Storage study; Quality analysis